The Influence of in the Dose Response of Radiation-Induced Apoptosis, DNA Repair and Genomic Stability in Murine Haematopoietic Cells - Jennifer A. Lemon; Kristina Taylor; Kyle Verdecchia; Nghi Phan; Douglas R. Boreham (SAGE Publishing, 2014)
Apoptotic and DNA damage endpoints are frequently used as surrogate markers of cancer risk, and have been well-studied in the Trp53+/− mouse model. We report the effect of differing Trp53 gene status on the dose response of ionizing radiation exposures (0.01-2 Gy), with the unique perspective of determining if effects of gene status remain at extended time points. Here we report no difference in the dose response for radiation-induced DNA double-strand breaks in bone marrow and genomic instability (MN-RET levels) in peripheral blood, between wild-type (Trp53+/+) and heterozygous (Trp53+/−) mice. The dose response for Trp53+/+ mice showed higher initial levels of radiation-induced lymphocyte apoptosis relative to Trp53+/− between 0 and 1 Gy. Although this trend was observed up to 12 hours post-irradiation, both genotypes ultimately reached the same level of apoptosis at 14 hours, suggesting the importance of late-onset p53-independent apoptotic responses in this mouse model. Expected radiation-induced G1 cell cycle delay was observed in Trp53+/+ but not Trp53+/− . Although p53 has an important role in cancer risk, we have shown its influence on radiation dose response can be temporally variable. This research highlights the importance of caution when using haematopoietic endpoints as surrogates to extrapolate radiation-induced cancer risk estimation.